Imperial running dogs or wild geese reporters? : Irish journalists in South Africa (Historia, 2021)
In recent years there has developed ex nihil, and thanks in part to the Newspaper and Periodical History Forum of Ireland, a keen interest in the history of the Irish press. However, something of a lacuna exists when it comes to Irish journalists working in the British Empire. These fell into two categories: those who were war correspondents or who worked for a news-gathering agency; and those Irish journalists who settled in the empire. The latter were particularly numerous in British South African colonies and the adjoining Boer republics. This article looks at this phenomenon, where no fewer than 40 newspapers at one time or another had an Irish editor or Irish senior journalist. The article examines the reason for this prominence of Irish journalists, the factors which drew them to South Africa, as well the stance taken by them on political allegiance. The paper discusses differences between journalists in British Natal and the Cape and those in the Boer Transvaal and Orange Free State republics. The role of Irish war correspondents at the time of the Anglo-Boer War also features.  In die afgelope tyd het 'n ex nihil ontwikkel, en deels te danke aan die Newspaper and Periodical History Forum of Ireland, 'n besondere belangstelling in die geskiedenis van die Ierse pers. Maar ietwat van 'n lemte bestaan wanneer dit kom by Ierse joernaliste wat in the Britse Ryk gewerk het. Die val in twee kategoriee: die wat oorlogskorrespondente was en die wat vir nuus insamelings agentsakppe gewerk het; en die Ierse joernaliste wat hulle in die ryk gevestig het. Laasgenoemde was veral talryk in die Britse kolonies in Suid-Afrika en die Boere republieke. Die artikel ondersoek die fenomeen waar nie minder as 40 koerante een of ander tyd 'n Ierse redakteur of 'n senior Ierse joernalis gehad het. Die artikel ondersoek die redes vir die prominensie van Ierse joernaliste, die faktore wat hulle na Suid-Afrika gelok het sowel as die politieke posisie wat hulle ingeneem het. Daar is ook gekyk na die verskille tussen Ierse joernaliste in die Kaap, Natal, Transvaal en die Oranje Vrystaat. Die rol van Ierse journaliste gedurende die Anglo-Boereoorlog word ook ondersoek.
Keywords: Irish diaspora; Journalists; Joernaliste; Ierse diaspora; Media history; Media geskiedenis